An empirical investigation into the influences of psychological empowerment and overall job satisfaction on employee loyalty: the case of Malaysian front office receptionists / Mohd Onn Rashdi Abd Patah...[et al.] - Abd Patah, Mohd Onn Rashdi; Zain, Razlan Adli; Abdullah, Dahlan; Mohd Radzi, Salleh (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2009)
The hotel industry has the responsibility and role of increasing guest satisfaction with its services and products. This can be carried out through efficient service by frontline employees, particularly the Front Office receptionists. Developing an efficient workforce may depend on their sense of belonging or loyalty to the organization. There are many ways and means of developing employees’ levels of loyalty to their organization. Empowering employees and high job satisfaction levels are among the studied factors that influence positive employee outcomes. This study was conducted to examine the influences of psychological empowerment and overall job satisfaction on the employee loyalty of Front Office Receptionists in Kuala Lumpur 5-star hotels. A total of 210 questionnaires were distributed at 21 hotels rated as 5-star hotels in Kuala Lumpur, Malaysia. Results showed that employee psychological empowerment does not have any significant impacts on loyalty. However, the findings suggested that overall job satisfaction did have a significant influence on loyalty. Hotel managers might consider more competitive solutions in their effort to increase the employee’s loyalty, for example by enhancing participation in the departmental decision making, encourage creativity, implementing a better work environment and employment packages.